Sexual Harassment of Female Employees in The Workplace: Imperative For Stringent Legal And Policy Frameworks In Nigeria - Enobong Mbang Akpambang (Pancasila and Law Review, 2022)
The central objective of the article was to investigate the challenges posed by work-associated sexual intimidation of female workers and whether there were binding legislative and policy frameworks to address the problem in Nigeria. To achieve the aim, the study adopted both doctrinal and comparative approaches by evaluating some available literature in the area and comparing Nigeria’s position with some selected foreign jurisdictions with legislative provisions barring harassment. The article also adopted some theoretical models to explain the possible reasons for sexual harassment. It was discovered that the menace of sexual harassment at workplace has received a robust attention domestically and globally from researchers and organizations with available data showing that the despicable practice occur both in public and private establishments and that it has considerable negative effects on employers as well as on the health and psychological welfare of employees. The work revealed that unlike some other countries, Nigeria lacked precise anti-sexual harassment legislation and that the extant national legislative frameworks on sexual-related offences are inadequate to effectively curb the problem. Thus, the article recommended that there is need for stringent legal and policy frameworks to be put in place in Nigeria in order to tackle the hydra-headed problem of job-related sexual harassment as are obtainable in the three foreign jurisdictions examined in the paper.